Independent effects of early life adversity on social cognitive function in patients with schizophrenia - Peng, Xing; Hou, Wen-Peng; Ding, Yu-Shen; Wang, Qi; Li, Feng; Sha, Sha; Yu, Chen-Chao; Zhang, Xiu-Jun; Zhou, Fu-Chun; Wang, Chuan-Yue (Frontiers in Psychiatry, 2024)
The aim of this study was to investigate the impact of early life adversity on cognitive function in patients with schizophrenia, with a focus on social cognition (SC).Methods: Two groups of patients with schizophrenia were recruited and matched on sociodemographic and clinical characteristics. One group consisted of 38 patients with a history of childhood trauma (SCZ-ct), and the other group consisted of 35 patients without a history of childhood trauma (SCZ-nct). In addition, 39 healthy controls without a history of childhood trauma (HC-nct) were also recruited. The intelligence of the three groups was assessed using the Wechsler Abbreviated Scale of Intelligence (WAIS-RC) short version. The cognitive function evaluation was conducted using the MATRICS Consensus Cognitive Battery (MCCB), and early life adversity was measured using the Childhood Trauma Questionnaire-Short Form (CTQ) and Bullying Scale for Adults (BSA).Results: Patients with schizophrenia endosed significantly higher scores on the CTQ (F=67.61, p＜ 0.001) and BSA (F=9.84, p＜0.001) compared to the HC-nct. Analysis of covariance (ANCOVA) and post-hoc analyses revealed that SCZ-ct (F=11.20, p＜0.001) exhibited the most pronounced cognitive impairment among the three groups, as indicated in MCCB total scores and in the domain score of SC.CTQ exhibited a negative correlation with MCCB (r=-0.405, p < 0.001); SC was negatively correlated with physical abuse (PA) of CTQ (r=-0.271, p=0.030) and emotional abuse (EA) of BSA (r=-0.265, p=0.034) in the whole patient sample. Higher SC performance was significantly predicted by CT_total (Beta =-0.582, p＜0.001, 95% CI -0.96-0.46), and years of education (Beta=0.260, p =0.014, 95% CI 0.20-1.75) in schizophrenia.Conclusions: Besides familial trauma, schizophrenia patients appear to have a higher likelihood of experiencing bullying in their early life. These experiences seem to contribute significantly to their severe impairments in SC.